Transcultural adaptation and validation of the Stanford Presenteeism Scale for the evaluation of presenteeism for Brazilian Portuguese Adaptación transcultural y validación para el portugués brasileño del Stanford Presenteeism Scale para evaluación del presentismo Adaptação transcultural e validação para o português brasileiro do Stanford Presenteeism Scale para avaliação do presenteísmo - Heloisa Campos Paschoalin; Rosane Harter Griep; Márcia Tereza Luz Lisboa; Diana Corrêa Bandeira de Mello (Universidade de São Paulo, 2013)
OBJECTIVE: describe the process of transcultural adaptation and validation of the Stanford Presenteeism Scale for Brazilian Portuguese. METHODS: Methodological study of the cultural adaptation and validation of the tool which involved 153 nursing staff and included six aspects of equivalence, obtained through the following stages: translation, first version of consent, retranslation, specialist committee, pre-test, study of test-retest credibleness and dimensional validity. RESULTS: The stability of the items varied from moderate to almost perfect and the sequence constancy was almost perfect. Two factors were identified through the exploratory fact analysis: the first one included the physical aspects - completing work; and the second one the psychological aspects - avoided distraction . CONCLUSIONS: the results suggest adequacy of the tool in the Brazilian Portuguese version, indicating its use in the context of the study group and in similar groups, contributing to the study of evidences which consolidate strategies that favor the health conditions of the jobholders. OBJETIVO: describir el proceso de adaptación transcultural y validación para el portugués brasileño del Stanford Presenteeism Scale. MÉTODOS: se trata de un estudio metodológico de adaptación cultural y validación de instrumento en que participaron 153 trabajadores de enfermería, incluyendo seis aspectos de equivalencia obtenidos en las siguientes etapas: traducción, primera versión de consenso, retrotraducción, comité de especialistas, prueba piloto, estudio de confiabilidad prueba-reprueba y validez dimensional. RESULTADOS: La estabilidad de los ítems varió de moderado a casi perfecto y el de la escala fue casi perfecto. Dos factores fueron identificados por el análisis factorial exploratorio: el primero incluye los aspectos físicos - trabajo finalizado y el segundo a los aspectos psicológicos - concentración mantenida. CONCLUSIONES: los resultados sugieren que el instrumento es adecuado en la versión en portugués brasileño, indicando su uso en el contexto de la población de estudio y en poblaciones semejantes, contribuyendo así para el estudio de evidencias que contienen estrategias que favorezcan las condiciones de salud de los trabajadores. OBJETIVO: descrever o processo de adaptação transcultural e validação para o português brasileiro do Stanford Presenteeism Scale. MÉTODOS: trata-se de estudo metodológico de adaptação cultural e validação de instrumento que envolveu 153 trabalhadores de enfermagem, incluindo seis aspectos de equivalência, obtidos pelas seguintes etapas: tradução, primeira versão de consenso, retrotradução, comitê de especialistas, pré-teste, estudo de confiabilidade teste/reteste e validade dimensional. RESULTADOS: a estabilidade dos itens variou de moderado a quase perfeito e da escala foi quase perfeito. Dois fatores foram identificados pela análise fatorial exploratória: o primeiro incluiu os aspectos físicos - trabalho finalizado e o segundo incluiu os aspectos psicológicos - distração evitada. CONCLUSÕES: os resultados sugerem adequação do instrumento na versão em português brasileiro, indicando seu uso no contexto da população de estudo e em populações semelhantes, contribuindo para o estudo de evidências que embasem estratégias que favoreçam as condições de saúde dos trabalhadores.